054: IUD USE IN BANGLADESH: THE PARADOX OF NEED, DEMAND AND SUPPLY CONTINUUM. (24th August 2015) - Hossain, Azmal
Abstract : Background: While the overall use of contraceptives is satisfactory (61.2%) in Bangladesh, the use of intrauterine device (IUD) is surprisingly low (0.9%) against high discontinuation rate (48%). Despite some researches in the past, it is difficult to pinpoint why IUD has never been popular in Bangladesh. While the health care professionals prescribe (need) for more use of IUD as a cheap, highly effective, long-acting and reversible method of contraception, the experience reveals that clients aspirations and desires (demand) of quality services are not appropriately addressed in providing (supply) such services: from the community to the health facilities and from the field workers to the services providers. Objectives: The overall objective of the FGDs was to identify the factors that influence the uptake of IUD. The specific objectives were: (1) to identify the barriers that influences the uptake of IUD, (2) to know about the insights of the satisfied IUD clients on the IUD use, (3) to know about the insights of the field workers on the IUD use, (4) to know about the insights of the husbands of the satisfied IUD clients on the IUD use and (5) to explore the possibility of using IUD clients as the referrer of IUD and other LARC & PM methods. Methods: 5 FGDs 2 with IUD users, 1 with users' husbands, 2 with field workers were organized in two Upazilas: Chirirbandar and Khansama Upazila of Dinajpur districts with total 42 participants;5 male and 37 female. These areas were selected on the basis of the low IUD performances. Result: According to the study, there are inconsistences in the need, demand and supply continuum. We found that social stigma and misconceptions (God will not accept IUD users' prayers and also their funereal wouldn'tbe accepted by God; husband's lifetime may decrease if the wife uses IUD; IUD is poisonous and causes to develop cancer, etc.) about IUD is the main factor for low uptake of IUD. Besides, poor quality of service and spousal approval also play important negative role. The other factors are client's shyness, providers' bias, demotivation and information mess. Conclusion: To make IUD popular in Bangladesh, the study implies to undertake interventions in 3 levels: integrated demand generation activities to remove stigma and social barriers at the community level including promotion of personal hygiene practices to make the women ready for IUD use; quality improvement intervention at the supply side including referral and services for side effect and complication management at the nearest health facilities; and special effort of utilizing female doctors as the IUD providers to reposition IUD as a method of better choice in Bangladesh.